Post prandial glucose can be a substitute for HbA1c in low resource setting: answering the diagnostic dilemma - Kumar, Binay; Prasad, Nidhi; Shekhar, Ravi (International Journal of Research in Medical Sciences, 2021)
Achieving a strict glycaemic control is the key factor in diabetes management and associated complications. Although A1C is the best indicator of overall glycaemic control during the previous 2-3 months and remains the gold standard for assessing glycaemic control in patients with diabetes. But in low resource setting areas where HbA1c is a costlier affair, postprandial plasma glucose estimation can be a good alternative in estimating glycaemic control. By analyzing the results from many previous papers on glycaemic profiles, we conclude that contribution of postprandial plasma glucose was relatively high in patients with fairly good control of diabetes (HbA1c <7.5%) and decreased progressively with worsening diabetes (HbA1c >10.2%). Whereas the contribution of fasting plasma glucose showed a consistent contribution with increasing levels of HbA1c. So, we can understand that post-meal glycemia was a better predictor of good or satisfactory control of diabetes (HbA1c <7.5%) than was fasting glucose. Postprandial plasma glucose is the prominent contributor in patients with satisfactory to good control of diabetes, whereas the contribution of fasting plasma glucose increases with worsening diabetes. Hence, PPG is better in predicting overall glycaemic control in the absence of HbA1c.